Ethical Leadership and Followers’ Moral Judgment: The Role of Followers’ Perceived Accountability and Self-leadership - Steinbauer, Robert (Journal of business ethics, 2014)
A two stage model was developed and tested to explain how ethical leadership relates to followers’ ethical judgment in an organizational context. Drawing on social learning theory, ethical leadership was hypothesized to promote followers’ self-leadership focused on ethics. It was found that followers’ perceived accountability fully accounts for this relationship. In stage two, the relationship between self-leadership focused on ethics and moral judgment in a dual decision-making system was described and tested. Self-leadership focused on ethics was only related to moral judgment when followers use active judgment as opposed to their intuition. This provides support that a deliberate application of self-leadership focused on ethics leads to higher moral judgment. Theoretical and practical implications as well as future research opportunities are discussed.